Simple Graphical Methods to Learn Trigonometry - Yeap, Kim Ho (Journal of Advanced Research in Signal Processing and Applications, 2021)
In this paper, two simple graphical methods to teach and learn trigonometry are presented. The paper is divided into two parts. The first part proposes a graphical approach to memorize the waveforms and the values of the three main trigonometric functions (i.e. tangent, sine, and cosine) when the angle is at 90 o . In the second part of the paper, a triangular model has been developed to allow students to memorize trigonometric identities with ease. Five trigonometric identities, namely, the reciprocal, quotient, Pythagorean, product, and derivative identities have been incorporated into the model. By perceiving the model from different lights, the relationships among these five identities could be easily correlated. How to cite this article: Yeap KH. Simple Graphical Methods to Learn Trigonometry . J Adv Res Sig Proc Appl 2020; 2(2): 15-18